Reappraisal of classification of distal cholangiocarcinoma based on tumour depth. Issue 7 (24th April 2018) - Aoyama, H.; Ebata, T.; Hattori, M.; Takano, M.; Yamamoto, H.; Inoue, M.; Asaba, Y.; Ando, M.; Nagino, M.; ,
Abstract : Background: In the eighth edition of the AJCC cancer staging classification, the T system for distal cholangiocarcinoma (DCC) has been revised from a layer‐based to a depth‐based approach. The aim of this study was to propose an optimal T classification using a measured depth in resectable DCC. Methods: Patients who underwent pancreatoduodenectomy for DCC at 32 hospitals between 2001 and 2010 were included. The distance between the level of the naive bile duct and the deepest cancer cells was measured as depth of invasion (DOI). Invasive cancer foci were measured as invasive tumour thickness (ITT). Log rank χ 2 scores were used to determine the cut‐off points, and concordance index (C‐index) to assess the survival discrimination of each T system. Results: Among 404 patients, DOI was measurable in 182 (45·0 per cent) and ITT was measurable in all patients, with median values of 2·3 and 5·6 mm respectively. ITT showed a positive correlation with DOI ( r S  = 0·854, P  < 0·001), and the cut‐off points for prognosis were 1, 5 and 10 mm. Median survival time was shorter with increased ITT: 12·4 years for ITT below 1 mm, 5·2 years for ITT at least 1 mm but less than 5 mm, 3·0 years for ITT at least 5 mm but less than 10 mm, and 1·5 years for ITT 10 mm or more ( P  < 0·001). This classification exhibited more favourable prognostic discrimination than the T systems of the seventh and eighth editions of the AJCC (C‐index 0·646, 0·622 and 0·624 respectively). Conclusion: ITT is an accurate approach for depth assessment in DCC. The four‐tier ITT classification with cut‐off points of 1, 5 and 10 mm seems to be a better T system than those in the seventh and eighth editions of the AJCC classification. Abstract : Better for T staging